'The Big Island Model': Resident experiences of a novel permanent supportive housing model for responding to rural homelessness. (26th July 2022) - Marshall, Carrie Anne; McKinley, Caitlyn; Costantini, Jacqueline; Murphy, Susanne; Lysaght, Rosemary; Hart, Brian P.
Abstract: Research on rural homelessness focuses primarily on describing the experiences and prevalence of homelessness in rural contexts, with little focus on intervention strategies. We conducted a case study of the 'Big Island Model' (BIM), a novel approach to providing housing and support to individuals experiencing homelessness that has been developed for, and reflects, a rural context. We interviewed 13 participants ( n  = 10 men; n  = 3 women) supported by the BIM using mixed interviews including qualitative and quantitative components exploring experiences of living within this model and aspects of psychosocial well‐being. Descriptive statistics were calculated to represent demographic data and participants' scores on standardised measures. Wilcoxon signed‐rank tests were conducted with threshold scores and population norms derived from existing literature to identify any differences between residents' median scores on each standardised scale and scores derived from published literature. Qualitative data were analysed using thematic analysis. On measures of meaningful activity, residents reported significantly lower levels of boredom ( p  < 0.01) and a greater degree of engagement in productivity ( p  < 0.01) compared with participants in other studies. Mental well‐being was reported to be higher ( p  < 0.05) and drug use was significantly lower than a low‐moderate range ( p  < 0.01). Community integration scores revealed significantly lower physical integration ( p  < 0.05) and significantly higher psychological integration than individuals who had transitioned to housing in another study ( p  < 0.001). Our analysis of qualitative interviews resulted in the identification of a central essence characterising residents' experiences: 'Becoming Through Belonging'. This essence was represented by four distinct themes: (1) the healing qualities of nature; (2) being meaningfully occupied; (3) living in a mutually supportive environment; and (4) this place is here to help.